2015
DOI: 10.1089/jmf.2014.3350
|View full text |Cite
|
Sign up to set email alerts
|

Cordyceps militarisEnhances Cell-Mediated Immunity in Healthy Korean Men

Abstract: Cordyceps militaris is a mushroom traditionally used for diverse pharmaceutical purposes in East Asia, including China, and has been found to be effective for enhancing immunity through various types of animal testing. The aim of this study is to determine the efficacy of C. militaris for enhancing cell-mediated immunity and its safety in healthy male adults. Healthy male adults were divided into the experimental group (n = 39), given 1.5 g/day of ethanol treated C. militaris in capsules, and the control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 22 publications
4
22
2
Order By: Relevance
“…Kwak et al [28] reported that changes in NK-cell activity were related to the level of serum IFN-γ. The changes in NK-cell activity and cytokines identified in this study are consistent with the results reported in several earlier studies [26,31,32] and cases [19,28,30,38,39]. Healthy adults who received Cordyceps militaris [31] supplements for 8 weeks or a mycelium extract of Cordyceps [32] for 8 weeks showed an increase in NK-cell activity without a change in cytokine levels, consistent with our findings in the current study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Kwak et al [28] reported that changes in NK-cell activity were related to the level of serum IFN-γ. The changes in NK-cell activity and cytokines identified in this study are consistent with the results reported in several earlier studies [26,31,32] and cases [19,28,30,38,39]. Healthy adults who received Cordyceps militaris [31] supplements for 8 weeks or a mycelium extract of Cordyceps [32] for 8 weeks showed an increase in NK-cell activity without a change in cytokine levels, consistent with our findings in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Healthy adults who received Cordyceps militaris [31] supplements for 8 weeks or a mycelium extract of Cordyceps [32] for 8 weeks showed an increase in NK-cell activity without a change in cytokine levels, consistent with our findings in the current study. Cordyceps militaris increased IL-2 and IFN-γ levels in addition to NK-cell activity in healthy males (average age, 36.5±11.2 years) after 4 weeks of supplementation [38], but after 12 weeks of intake, only NK-cell activity was increased in healthy males and females (average age 48.9±6.7 years [31]), similar to our findings. In other studies, intake of Chlorella [28] by healthy adults (WBC counts 4,000-8,000 cells/μL) for eight weeks increased cytokine levels (IFN-γ, interleukin-1β) in addition to increasing NK-cell activity.…”
Section: Discussionsupporting
confidence: 89%
“…It was reported that C . militaris fruit body extract enhances NK cell activity and T cell proliferation and partially increases Th1 cytokine secretion in healthy humans (H. J. Kang, Baik, Kim, et al, ). Animal studies demonstrated growth inhibitory effects of C .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that C. militaris fruit body extract enhances NK cell activity and T cell proliferation and partially increases Th1 cytokine secretion in healthy humans (H. J. Kang, Baik, Kim, et al, 2015). Animal studies demonstrated growth inhibitory effects of C. militaris fruit body extract on sarcoma and breast cancer; the effects are closely linked with suppression of Treg cells and increases of helper T cells, cytotoxic T cells, or NK cells (Jeong, Lee, Lee, et al, 2013;H.…”
Section: Introductionmentioning
confidence: 99%
“…The OPE was acquired from Changnyeong between August and September 2012, and passed through an OPE powder manufacturing process [15]. The OPE group was received 100 mg of quercetin [15] daily for 12 weeks, while placebo group was treated with identically-packaged soft capsules containing lactose mixture [16]. …”
Section: Methodsmentioning
confidence: 99%